PENGARUH MEDIA PEMBELAJARAN PENGENALAN TATA CARA WUDHU DAN SHOLAT BERBASIS ANIMASI 3 DIMENSI TERHADAP HASIL BELAJAR FIQIH KELAS 1 MADRASAH IBTIDAIYAH NEGERI 1 KARANGASEM - Ahda Audia; Nyoman Sugihartini; I Made Putrama (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2019)
This study aims to determine (1) differences in learning outcomes between students using learning media introduction to procedures for ablution and prayer based on 3-dimensional animation and students using lecture methods (2) knowing student responses after using learning media introduction to procedures for ablution and prayer based 3-dimensional animation. This type of research is a quasi-experimental (quasi-experimental) design with Post Test Only Control Group Design. Learning outcomes data were analyzed by conducting normality tests, homogeneity tests and t-tests. The results showed that the average results of the analysis of learning (experimental> control) with cognitive values (81.46> 70), psychomotor values (95> 89.23), affective values (79.2> 70.83) and student responses from the application of learning media in Fiqh subjects is very positive, namely 21 out of 25 students.  Keywords : Learning Media, Fiqh Learning Results, Student Response